Analisis Ketersediaan Dan Kebutuhan Air Di Das Cisangkuy - Mariana Lusiana Resubun; Enni Dwi Wahyunie; Suria Darma Tarigan (Musamus AE Featuring Journal, 2019)
Flooding in the rainy season and a drought that occurred in the dry season shows the distribution discharge river that is not evenly throughout the year. The event of floods and droughts happened in Cisangkuy watershed will affect the availability of water in fulfilling 6 important sectors of supporting human life, which is: domestic demand for water, agricultural land for farming, freshwater pounds, farm, industry and maintenance of rivers. Analysis of supply and demand for water in this research aims to review the availability and water demand in Cisangkuy watershed , and also water conservation effort with integrated water management. Methods used in this research is a observation method. The result showed there are scarce water ( deficit) in 2005, 2010 and 2015, each of 76 962 026 m3year-1 111 189 540 m3year-1 and 170 215 063 m3year-1.